Transformation of Islamic Boarding Schools as Islamic Education Institutions in Indonesia - Ahmad Musaddad (Journal of Islamic Education Research, 2023)
Islamic boarding schools in Indonesia, known as "pesantren," represent the oldest Islamic educational institutions that continue to evolve to meet the needs of modern society while preserving their unique educational substance. The journey of these institutions to achieve legal recognition from the government has been challenging and has experienced a long and dynamic process. This study employs a literature review approach involving key steps such as identification, selection, evaluation, and synthesis of relevant literature sources on the research topic. The findings reveal that pesantren have a long history and unique characteristics closely related to the development of Islam in Indonesia. The development of pesantren can be categorized into three groups: salaf (traditional), Khalaf (transitional), and integrated. The Mu'adalah Educational Unit is an innovation that combines religious and general curricula in a balanced manner, reflecting the need for pesantren to adapt to the changing times. Initiatives such as Pesantren Luhur, Ma'had 'Aly, and Ma'had 'Aly as higher education institutions demonstrate the efforts of Pesantren to develop structured and systematic religious higher education. Overall, this transformation illustrates the endeavours of pesantren to adapt and integrate religious and general education, improve the quality and relevance of education, and contribute to the development of society and the Indonesian nation globally.